2022
DOI: 10.1109/access.2022.3159977
|View full text |Cite
|
Sign up to set email alerts
|

Multi-UAV Assisted IoT NOMA Uplink Communication System for Disaster Scenario

Abstract: Unmanned aerial vehicle (UAV) communication has become a prominent technology that can effectively assist in IoT systems. The inherent features of UAV such as mobility, flexibility, and fast deployment make it preferable for emergency Internet of Things (IoT) applications. In this paper, we consider a multi-UAV assisted wireless network to support uplink communication for IoT devices distributed over a disaster area. The network involves two types of UAVs: sector UAV (SU) and anchor UAV (AU). The SU hovers at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, many researchers have assumed a stationary node, even if the target is a user device, i.e., an inherently mobile node, because its speed is naturally much slower than that of a UAV. In the communication between a UAV and stationary sensors [111,120,121,131,138,143,148,151,153,157,158,162,[166][167][168][169][170][171][172][173], the sensing area is divided into clusters and sensing nodes into cluster members, cluster heads, and relay nodes, responsible for data sensing, collection, and forwarding, respectively [172]. Clustering can reduce energy consumption, increase network scalability, extend battery life, decrease network delay, and boost throughput [174,175].…”
Section: Iotmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many researchers have assumed a stationary node, even if the target is a user device, i.e., an inherently mobile node, because its speed is naturally much slower than that of a UAV. In the communication between a UAV and stationary sensors [111,120,121,131,138,143,148,151,153,157,158,162,[166][167][168][169][170][171][172][173], the sensing area is divided into clusters and sensing nodes into cluster members, cluster heads, and relay nodes, responsible for data sensing, collection, and forwarding, respectively [172]. Clustering can reduce energy consumption, increase network scalability, extend battery life, decrease network delay, and boost throughput [174,175].…”
Section: Iotmentioning
confidence: 99%
“…In [134], the hovering region was enhanced through a tether, ensuring longer flight times. Six nonorthogonal multiple access (NOMA) schemes have been proposed by the authors in our sample, with the aim of minimizing the transmitting power of users and mobile devices [126] as well as maximizing the achievable rate of devices [129,157,166], throughput [173], and energy efficiency [130]. Researchers [127,128] have targeted the maximization of the number of connected mobile devices by extending network coverage.…”
Section: Resource Allocation For Mobile Devicesmentioning
confidence: 99%
“…The authors suggested that path aggregation networks (PANet) show promise in real-time applications when solving nonconvex problems associated with optimal 3D placement in communication networks. A Multi-UAV assisted NOMA wireless network uplink communication for IoT devices is proposed by Barick and Singhal for disaster scenarios [345]. NOMA allows the improvement of the uplink capacity of the system by jointly optimizing the position of the UAVs and the power control of the IoT devices.…”
Section: ) 5g Mmwave Uav-assisted Communication Networkmentioning
confidence: 99%
“…[14] proposes a mathematical model to find the inter UAV distances in a multi-UAV network to maximize the coverage. In [15], the authors consider a network topology for monitoring a post-disaster scenario. This gives a mathematical model to decide the optimal UAV positions for providing coverage with minimum transmitting power.…”
Section: Related Workmentioning
confidence: 99%